2020
DOI: 10.1364/oe.408310
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of the impact of the light source on the measurement of short-term average crosstalk in homogeneous single-mode multi-core fibers

Abstract: This work compares the random time-varying crosstalk in homogeneous multi-core fibers measured using different types of light sources with linewidths ranging from 100 Hz to 2.5 MHz. We show that the frequency stability of the light source plays a significant role on the quality of short-term average crosstalk measurements with no observable impact from laser linewidth. We also compare the use of filtered amplified spontaneous emission noise and coherent light sources for crosstalk measurements. The former are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In DD orthogonal frequency division multiplexing systems, photodetected ICXT power variations induced by phase noise that exceed 20 dB have been observed with a time duration scale that is much shorter than the scale of the time variation typical of ICXT mechanism [17]. More recently, it was shown that the choice of the light source used for the STAXT measurements has significant impact on their precision [30].…”
Section: Introductionmentioning
confidence: 99%
“…In DD orthogonal frequency division multiplexing systems, photodetected ICXT power variations induced by phase noise that exceed 20 dB have been observed with a time duration scale that is much shorter than the scale of the time variation typical of ICXT mechanism [17]. More recently, it was shown that the choice of the light source used for the STAXT measurements has significant impact on their precision [30].…”
Section: Introductionmentioning
confidence: 99%